Tourniquet Use in a Civilian Emergency Medical Services Setting: A Descriptive Analysis of the Boston EMS Experience. (3rd July 2015) - Kue, Ricky C.; Temin, Elizabeth S.; Weiner, Scott G.; Gates, Jonathan; Coleman, Melissa H.; Fisher, Jonathan; Dyer, Sophia
Abstract Introduction. Despite the resurgence of early tourniquet use for control of exsanguinating limb hemorrhage in the military setting, its appropriate role in civilian emergency medical services (EMS) has been less clear. Objective. To describe the experience of prehospital tourniquet use in an urban, civilian EMS setting. Methods. A retrospective review of EMS prehospital care reports was performed from January 1, 2005 to December 1, 2012. Data, including the time duration of prehospital tourniquet placement, EMS scene time, mechanisms of injury, and patient demographics, underwent descriptive analysis. Outcomes data for participating receiving hospitals were also reviewed. Results. Ninety-eight cases of prehospital tourniquet use were identified. The most common causes of injury were penetrating gunshot or stabbing wounds (67.4%, 66/98); 7.1% (7/98) of cases were due to blunt trauma; 23.5% (23/98) of cases were from nontraumatic hemorrhage related to uncontrolled hemodialysis shunt or wound bleeding; 45.4% (44/97) of cases were placed on a lower extremity; 54.6% (53/97) were placed on an upper extremity. Placement was successful in hemorrhage control in 91% (87/95, 95%CI: 85.9–97.3%) of cases. The average prehospital tourniquet placement time was 14.9 minutes. Half of all tourniquet placements were performed by basic life support providers. Hospital follow-up was available for 96.9% (95/98) of cases. Of these, the tourniquet was removed by EMS in 3.2% (3/95), the emergency department in 54.7% (52/95), or in the operating room (OR) in 31.6% (30/95) of the time; 46.7% (14/30) of these OR cases had a documented vascular injury needing repair. Ten deaths with hospital follow-up data were identified, none of which were due to tourniquet use. There was one case of forearm numbness potentially due to nerve injury and one case with potential vascular complication, representing an overall complication rate of 2.1% (2/95). Conclusion. The early use of tourniquets for extremity hemorrhage in an urban civilian EMS setting appears to be safe, with complications occurring infrequently.